Causes De La Reticence Des Etudiants Marocains VisA-Vis De La Geologie; Cas De La Faculte Des Sciences Dhar Mahraz De Fes - Imane Chmanti-Houari; Mohammed Oudrhiri Hassani; Hassan Lachkhem; Ahmed Sayad (European Scientific Journal, ESJ, 2016)
In this work, we try to diagnose the causes of reluctance of Moroccan students’ towards the geology. To achieve our goal, a study was conducted on the first year students of the Faculty of Science Dhar El Mehraz. Then a questionnaire was made and administered to professors and first year students. The obtained results revealed that the students' reluctance is mainly due to pedagogical difficulties.